Impact of hepatitis C treatment on long-term outcomes for patients with hepatocellular carcinoma: a United States Safety Net Collaborative Study. Issue 3 (March 2021) - Turgeon, Michael K.; Lee, Rachel M.; Gamboa, Adriana C.; Yopp, Adam; Ryon, Emily L.; Goel, Neha; Wang, Annie; Lee, Ann Y.; Luu, Sommer; Hsu, Cary; Silberfein, Eric; Maithel, Shishir K.; et al.
Abstract: Background: Widespread HCV treatment for hepatocellular carcinoma (HCC) patients remains limited. Our aim was to evaluate the association of HCV treatment with survival and assess barriers to treatment. Methods: Patients in the U.S. Safety Net Collaborative with HCV and HCC were included. Primary outcome was overall survival (OS). Secondary outcomes were recurrence-free survival (RFS) and barriers to receiving HCV treatment. Results: Of 941 patients, 57% received care at tertiary referral centers (n=533), 74% did not receive HCV treatment (n=696), 6% underwent resection (n=54), 17% liver transplant (n=163), 50% liver-directed therapy (n=473), and 7% chemotherapy (n=60). HCV treatment was associated with improved OS compared to no HCV treatment (70 vs 21 months, p<0.01), persisting across clinical stages, HCC treatment modalities, and treatment facilities (all p<0.01). Surgical patients who received HCV treatment had improved RFS compared to those who did not (91 vs 80 months, p=0.03). On MVA, HCV treated patients had improved OS and RFS. On MVA, factors associated with failure to receive HCV treatment included Black race, higher MELD, and advanced clinical stage (all p<0.05). Conclusion: HCV treatment for HCC patients portends improved survival, regardless of clinical stage, HCC treatment, or facility type. Efforts must address barriers to HCV treatment.